The multiple mediating roles of depression and grandchild care in the relationship between social participation and cognitive function among middle-aged and elderly Chinese: an empirical study based on CHARLS 2020 data - Zhou, Sumei; Deng, Tianfang; Shao, Shirong; Zeng, Zhi (Frontiers in Aging Neuroscience, 2025)
BackgroundWith global and Chinese populations aging rapidly, maintaining cognitive function among middle-aged and elderly individuals has become a critical health priority. Understanding the factors influencing cognitive health is crucial for developing effective health policies and interventions.ObjectivesThis study investigates the impact of social participation on cognitive function among middle-aged and elderly individuals, examining the mediating effects of depression and grandchild care. Given the potential variation in these effects across different demographic and socioeconomic groups, this study also explores subgroup differences to provide targeted policy recommendations.MethodsData from the 2020 China Health and Retirement Longitudinal Study (CHARLS) were used to analyze the relationship between social participation and cognitive function. Ordinary Least Squares (OLS) and stepwise regression models were employed, with robustness checks conducted using 2SLS regression.ResultsThe study included 17,962 participants aged 45 and above. Baseline regression results indicate that social participation significantly enhances cognitive function (β = 0.417, p = 0.001) after adjusting for confounding factors. Subgroup analysis revealed that the cognitive benefits of social participation were more pronounced among individuals residing in the western region, those aged 60 and above, high-income groups, and rural populations. Mediation analysis showed that depression played a more substantial mediating role (β = –0.109, p = 0.001), while grandchild care exhibited a statistically significant but relatively small mediation effect (β = 0.004, p = 0.001).ConclusionSocial participation not only directly improves cognitive function but also indirectly enhances it by reducing depression and increasing grandchild caregiving engagement among middle-aged and elderly individuals. However, while the mediating effect of grandchild care is statistically significant, its effect size remains relatively small, suggesting that its overall contribution to cognitive function should be interpreted with caution. In contrast, depression demonstrates a more substantial mediating effect, highlighting the critical role of mental health in cognitive aging. Given these findings, policy should prioritize interventions that mitigate depression as a primary pathway for enhancing cognitive function in aging populations. Expanding social participation opportunities should be a key strategy, particularly in the central and eastern regions, among individuals under 60 years old, those with lower income levels, and urban residents, to ensure equitable access to cognitive health benefits. Additionally, while grandchild caregiving may serve as a meaningful form of social engagement, its effects on cognitive function appear to be complex and context-dependent. Future research should explore the long-term impact of caregiving intensity and emotional burden on cognitive health to better inform aging policies and intergenerational support programs.